2021
DOI: 10.3390/pathogens10040414
|View full text |Cite
|
Sign up to set email alerts
|

Application of Quantitative-PCR to Monitor Netpen Sites in British Columbia (Canada) for Tenacibaculum Species

Abstract: Tenacibaculum are frequently detected from fish with tenacibaculosis at aquaculture sites; however, information on the ecology of these bacteria is sparse. Quantitative-PCR assays were used to detect T. maritimum and T. dicentrarchi at commercial Atlantic salmon (Salmo salar) netpen sites throughout several tenacibaculosis outbreaks. T. dicentrarchi and T. maritimum were identified in live fish, dead fish, other organisms associated with netpens, water samples and on inanimate substrates, which indicates a ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…(Apablaza et al, 2017). Similar tenacibaculosis coinfections have been reported in salmon farms in Norway (Olsen et al, 2011;Småge et al, 2016b), Australia (Wilson et al, 2019), and Canada (Nowlan et al, 2021).…”
Section: Presumptive and Confirmative Diagnostic Procedures For Tenac...supporting
confidence: 66%
See 1 more Smart Citation
“…(Apablaza et al, 2017). Similar tenacibaculosis coinfections have been reported in salmon farms in Norway (Olsen et al, 2011;Småge et al, 2016b), Australia (Wilson et al, 2019), and Canada (Nowlan et al, 2021).…”
Section: Presumptive and Confirmative Diagnostic Procedures For Tenac...supporting
confidence: 66%
“…Weight also impacts susceptibility; fish weighing 2-80 g are more susceptible to acute infection, whereas fish over 100 g seem less susceptible (Avendaño- Herrera et al, 2006a). Further influencing infection severity and mortality rates are temperature, water parameters, rearing conditions, stress, and interfering parasitic infestations (Nowlan et al, 2021). In a presumptive diagnosis, the main macroscopic lesions associated with T. maritimum infection are external and include ulcerative skin, tissue necrosis, mouth erosion, tail and fin rots, and necrosis of the gills and eyes [see review by Bernardet (1998); Avendaño-Herrera et al, (2006a)].…”
Section: Presumptive and Confirmative Diagnostic Procedures For Tenac...mentioning
confidence: 99%
“…Often when a new niche is available for colonization, bacteria that have similar resource requirements will compete, where three long-term consequences are often described (exclusion [a winner], assignment of metabolic niches, or spatial separation of bacteria) [18]. Contamination between tanks could have occurred, potentially through contaminated water, with Tdic as the winner and can be supported by the fact that Tdic is a common isolate from fish with mouthrot in BC [8]. This potential phenomenon requires further investigation, perhaps using dual infections and monitoring isolates over time with qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Several Tenacibaculum bacterial species are putative pathogens associated with tenacibaculosis in fishes [1][2][3][4][5][6]. In British Columbia (Canada; BC), Tenacibaculum species are commonly isolated from Atlantic salmon (Salmo salar L.) with mouthrot; a regional, clinical presentation of tenacibaculosis, often characterized by epidermal ulcerations and development of yellow plaques around the mouth [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Early research into the causal agent of mouthrot in BC identified Tenacibaculum maritimum as the responsible pathogen (Frisch et al, 2018;Wynne et al, 2020), with experimental trialsusing T. maritimum isolates collected from outbreaks on Atlantic salmon farms in BCsuccessfully inducing mouthrot in exposed Atlantic salmon (Frisch et al, 2018). However, new molecular assays have recently been developed to identify the presence and abundance of other Tenacibaculum species, including T. dicentrarchi and T. finnmarkense (Avendaño-Herrera et al 2016;Smage et al, 2016;Bridel et al, 2018;Nowlan, 2020). These have both been detected on salmon farms, can co-occur with T. maritimum, and may be responsible for some cases of tenacibaculosis (Alvarez and Santos, 2018;Avendaño-Herrera et al 2016;Smage et al, 2016Smage et al, , 2018Olsen et al, 2017;Mimeault et al, 2020).…”
Section: Introductionmentioning
confidence: 99%